Literature on the Margins: Russian Fiction in the Nineties - Mark Lipovetsky (Studies in 20th & 21st Century Literature, 2000)
Despite shrinkage in print runs and readership, canonical Literature during the 1990s developed along three major lines that connected writers of various generations in both aesthetics and philosophy: realism, exemplified in Georgii Vladimov's prize-winning novel, The General and His Army (1994); postmodernism, richly represented in the fiction of Vladimir Sorokin, Viktor Pelevin, and Vladimir Sharov; and neosentimentalism, as derived from the naturalism of early perestroika, most consistently embraced by Liudmila Petrushevskaia, Liudmila Ulitskaia, and, in his paternal profession de foi, one of Russia's chief theorists of postmodernism, Mikhail Epshtein. All three tendencies aspired to the status of mainstream, which they failed to attain, owing to a fundamental instability that chaos theory has labeled a "bifurcation cascade." Inasmuch as that stage, according to specialists in chaos theory, leads to irreversible changes that effect a high level of stability, the outlook for Russian literature at century's end might be less bleak than prophesied by doomsayers.
Keywords: Russian fiction; 90s; aesthetics; philosophy; realism; Georgii Vladimov; The General and His Army; postmodernism; Vladimir Sorokin; Viktor Pelevin; Vladimir Sharov; neosentimentalism; naturalism; perestroika; Liudmila Petrushevskaia; Liudmila Ulitskaia; profession de foi; Mikhail Epshtein; bifurcation cascade